(untitled) (Semiárida, 2020)
In this contribution 23 species of naturalized and adventive plants, are cited for first time tor La Pampa. The synonymy, a short description, the distribution, and the dispersal forms are given. The iconography and a boucher are included. A Iist of 13 species who were cited for J. Williamson (1967) with the iconography and a voucher, is attached.